Standardized ecological indicators to assess aquatic food webs: The ECOIND software plug-in for Ecopath with Ecosim models. (March 2017) - Coll, M.; Steenbeek, J.
Abstract: Ecological indicators are useful tools to analyse and communicate historical changes in ecosystems and plausible future scenarios while evaluating environmental status. Here we introduce a new plug-in to the Ecopath with Ecosim (EwE) food web modelling approach, which is widely used to quantitatively describe aquatic ecosystems. The plug-in (ECOIND) calculates standardized ecological indicators. We describe the primary functionality of ECOIND and provide an example of its application in both static and temporal-spatial dynamic modelling, while we highlight several related features including a new taxonomy input database (species traits) and the ability to analyse input uncertainty on output results. ECOIND adds new capabilities to the widely used EwE food web modelling approach and enables broadening its applications into biodiversity and conservation-based frameworks to contribute to integrated ecosystem analyses. Highlights: Ecological indicators communicate historical and future changes in ecosystems. The ECOIND plug-in calculates standardized ecological indicators from Ecopath with Ecosim (EwE) food web models. EwE applications are expanded into biodiversity and conservation-based frameworks.